The impact of college experience on female students’ self-perceived employability in STEM majors - Wen, Wen; Zhou, Lu; Hu, Die; Zhang, Mingyu; Yan, Zehua; Tang, Xiaofeng (Frontiers in Psychology, 2023)
In China, although women have made significant progress in pursuing STEM degrees in recent years, they continue to face challenges in the workforce. Given the importance of the selfperceived employability (SPE) of female STEM students in China, the research questions are: How do curriculum experience, extracurricular experience, and faculty supportive activities affect the SPE of female STEM students in Chinese universities? To what extent does university stratification affect the relationship between college experience and female STEM students' SPE?We analysed the 2018 data of the Chinese College Student Survey consisting of a sample of 59,066 students, and six focus group interviews. The findings suggest that men benefit more in terms of the increase in SPE from most types of college activities and support. This study focuses on the underrepresentation of female students in STEM disciplines from an intersectional perspective that considers the effect of gender and university tier. It provides valuable evidence for administrators and policymakers to critically assess the ramifications of university stratifications, aiming to mitigate negative effects on specific student groups within society.